Art therapy with an African American female combat veteran experiencing effects of mild traumatic brain injury and post-traumatic stress - Chilton, Gioia; DeLucia, Jennifer Marie; Tompkins, Myissha (Frontiers in Psychiatry, 2025)
This retrospective case study explored the use of art therapy (AT) with an AfricanAmerican female combat veteran experiencing the effects of mild traumatic brain injury (mTBI) and co-occurring post-traumatic stress disorder (PTSD). The study aimed to understand how culturally informed military AT functions in the treatment of a female service member with mTBI and PTSD. Qualitative data were collected from artwork, case notes, and the therapist’s clinical reflections. Quantitative data were collected using the Emotion Regulation Strategies for Artistic Creative Activities Scale (ERS-ACA). Thematic analysis and ERS-ACA results revealed several themes. The results illustrated that art therapy supported the client to express her needs, strengths, and treatment progress; it facilitated emotional expression; supported the expression of cultural identity; and provided a method for communicating her needs to others outside of art therapy sessions. This case study underscores the potential for utilizing standardized art therapy treatment methods to benefit military-connected individuals with similar conditions.